Activist systems: Futuring with living models. (June 2016) - Roudavski, Stanislav; Jahn, Gwyllim
This article considers how computational simulation can be used to amplify imagination and make its effects sharable, persuasive and activist. It argues that this is not only possible but important for the future of design and introduces the concept of living models as a device that can express the futuring potential of such simulations. Developing this argument, the article explores whether, by postponing top-down rationalisms in favour of a 'methodological naiveté', designers can gain the capacity to uncover and engage with the unusual participants of the complex dynamic assemblages they aim to change. When designers collaborate with the agencies of the living models they deploy, the outcomes prove useful for the exploration of alternative values and worldviews. Explorations of this kind are significant because human designs need to improve their integrations with existing complex systems and are innovative in their ambition to see creative agency in non-human actors. In a practical demonstration of such approaches, the experiments in generative computation presented in this article illustrate that design creativity occurs through humans but not entirely because of them.